Thermal and Infrared Studies of Garnierite from the Soroako Nickeliferous Laterite Deposit, Sulawesi, Indonesia - Sufriadin, Sufriadin; Idrus, Arifudin; Pramumijoyo, S.; Warmada, I. W.; Nur, I.; Imai, A.; Imran, A. M.; Kaharuddin, Kaharuddin (Geological Agency, 2012)
DOI:Â 10.17014/ijog.v7i2.137Mineralogical characterization of some garnierite samples from Soroako have been conducted using X-ray diffraction, thermal analysis, and infrared spectroscopy methods. XRD patterns reveal the samples mainly containing the mixture of kerolite (talc-like phase) and serpentine with minor smectite, sepiolite, and silica. Thermal analyses of garnierite samples indicated by DTA curves are in good agreement with patterns that have been reported in literature. Three endothermic peaks normally occur in the ranges between 58Âº C and <800Âº C illustrating three steps of weight losses: adsorbed, bound, and hydroxyl/crystal water. One additional weight loss in low temperature region of sepiolite is corresponding to the lost of zeolitic water. Infrared spectra appeared in 3800 - 3200 cm-1 region generally exhibit broad absorption bands, indicating low crystallinities of studied samples and can be assigned to the presence of hydroxyl group bonded to octahedral coordination mainly Mg atom. The bands observed at 1660 cm-1, 1639 cm-1, 1637 cm-1, and 1633 cm-1 in all samples indicate water molecules. FTIR spectra displaying the strong bands at 1045 cm-1, 1038 cm-1, and 1036 cm-1 could be related to the presence of Si-O-Si bonds linking to tetrahedral coordination. The strong absorption bands appeared at 511 cm-1, 505 cm-1, 499 cm-1, and 496 cm-1 in respective samples are attributed to divalent cation bonds (e.g. Mg, Ni-O). Both TG/DTA and FTIR seem to be the powerful tool in diagnosing the crystal chemistry of garnierite which is mainly composed of phyllosilicate minerals.